Differences between the winning and defeated handball teams in attack organisation - the final phase of the 2017 World Women`s Championship in Germany - Ohnjec, K.; Vuleta, D.; Kanjugovic, I.; Milanovic, D. (World Congress of Performance Analysis of Sport XII, 2018)
This research was conducted to determine how different types of attack, duration of attack as well as types of their endings contribute to the differences between the winning and defeated teams at the end of the World Women`s Handball Championship 2017. Out of the total of 330 attacks played in the final phase of the Championship (2 semi-final matches, bronze medal match and final match), the winning teams played a total of 162 attacks, whereas the defeated teams had four attacks more, I.e. 168 attacks. The winners played a total of 138 positional attacks (PN) and 24 transitional (TN) attacks. The defeated teams played a total of 138 positional attacks and 30 transitional, I.e. fast-breaks. The obtained results point to the great equality of the best world women`s handball teams. The results of Kruskal-Wallis test and ANOVA indicate the statistically significant difference in attack duration between the winning and defeated teams where the winners performed their attacks, on average, for a longer period of time. They respected the gradual nature of attack building-up, performed fewer fast-breaks, paid full attention to the stage of attack preparation against the organized defence, used many rhythm and movement speed changes, dynamically varied their mobility with fast transfer of ball, thus creating most appropriate situations for attack realisation (attack endings).